Implementasi Total Productive Maintenance sebagai Upaya Peningkatan Efektivitas dan Pencegahan Breakdown Mesin Multi Pack PT PCI dengan Analisis Data - Muhammad Rizki Fitridiansyah; Rusindiyanto (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
This study discusses the implementation of Total Productive Maintenance (TPM) as an effort to increase effectiveness and prevent breakdowns on Multi Pack Machines at PT PCI. During the observation process, it was found that the downtime duration was still quite high and affected the smooth production. Based on the recapitulation results using Microsoft Excel, the total downtime on the Multi Pack Machine PL 2 reached 555 minutes, which indicates the need for an evaluation of the current maintenance pattern. Through the implementation of TPM pillars, specifically Autonomous Maintenance, Planned Maintenance, and Quality Maintenance, this study highlights the importance of operator and maintenance team involvement in maintaining stable machine conditions. Downtime data was then analyzed using Excel to identify dominant causes through Pareto diagrams and root cause analysis. The results showed that several main factors causing disruptions could be clearly mapped so that corrective actions could be directed more precisely. The implementation of TPM was proven to be able to reduce the potential for recurrent damage and contribute to increasing the machine's OEE value.